Strategi Pemasaran dan Target Pasar dalam Meningkatkan Daya Saing UMKM : (Studi Kasus Pada Pisang Coklat Meler UMSU) - Revita Sari; Mela Carisa (Pusat Riset dan Inovasi Nasional, 2025)
MSMEs are expected to be responsive and able to understand the market so they can survive in competition. Basically, marketing strategy is a way to show the superiority of a product which aims to win sustainable marketing competition for both goods and service production companies. One of the MSMEs that runs this business is Meler Chocolate Bananas. The problem formulation for this research is: What is the marketing strategy and target market carried out by Meler Chocolate Banana MSMEs to increase the competitiveness of their business? This research aims to determine the marketing strategy and target market for Meler Chocolate Banana MSMEs in increasing their business competitiveness. It is hoped that this research will have theoretical and practical benefits that will help in implementing marketing strategies and market targets in increasing business competitiveness. This research uses a type of descriptive qualitative research, where the sample determination technique uses a purposive sampling method, the researcher analyzes the data by conducting Data Reduction, Data Display, SWOT Analysis, and Drawing Conclusions. The impact of marketing strategies in increasing the competitiveness of Piscok Meler MSMEs, through appropriate marketing strategies increases the competitiveness of brown banana businesses by dividing the market into smaller segments. So companies can identify customer groups that have similar needs and characteristics.